Helicobacter pylori management in ASEAN: The Bangkok consensus report. Issue 1 (28th December 2017) - Mahachai, Varocha; Vilaichone, Ratha‐korn; Pittayanon, Rapat; Rojborwonwitaya, Jarin; Leelakusolvong, Somchai; Maneerattanaporn, Monthira; Chotivitayatarakorn, Peranart; Treeprasertsuk, Sombat; Kositchaiwat, Chomsri; Pisespongsa, Pises; Mairiang, Pisaln; Rani, Aziz; et al.
Abstract: Helicobacter pylori ( H. pylori ) infection remains to be the major cause of important upper gastrointestinal diseases such as chronic gastritis, peptic ulcer, gastric adenocarcinoma, and mucosa‐associated lymphoid tissue lymphoma. H. pylori management in ASEAN: the Bangkok consensus report gathered key opinion leaders for the region to review and evaluate clinical aspects of H. pylori infection and to develop consensus statements, rationales, and grades of recommendation for the management of H. pylori infection in clinical practice in ASEAN countries. This ASEAN Consensus consisted of 34 international experts from 10 ASEAN countries, Japan, Taiwan, and the United States. The meeting mainly focused on four issues: (i) epidemiology and disease association; (ii) diagnostic tests; (iii) management; and (iv) follow‐up after eradication. The final results of each workshop were presented for consensus voting by all participants. Statements, rationale, and recommendations were developed from the available current evidence to help clinicians in the diagnosis and treatment of H. pylori and its clinical diseases.